PENGARUH PELAYANANAN FISKUS DAN PENERAPAN E-FILLING TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KESADRAN PAJAK SEBAGAI VARIABEL MODERASI DIKANTOR PELAYANAN PAJAK PRATAMA II KOTA PADANG - Nabila Asyifa Putri; Elfiswandi; Silvia Sari (STKIP Subang, 2026)
This study aims to analyze the effect of tax officer services and the implementation of e-filing on taxpayer compliance, with tax awareness serving as a moderating variable among individual taxpayers at the Tax Service Office (KPP) Pratama II Padang. The sampling technique employed the Slovin formula, resulting in a sample of 100 respondents. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression analysis and Moderated Regression Analysis (MRA). The data were processed using the Statistical Package for the Social Sciences (SPSS).The results indicate that tax officer services have a positive and significant effect on taxpayer compliance. Meanwhile, the implementation of e-filing does not have a positive and significant effect on taxpayer compliance. Furthermore, tax awareness does not moderate the relationship between tax officer services and taxpayer compliance, nor does it strengthen the relationship between the implementation of e-filing and taxpayer compliance